A processing technology and application of high-strength and high-toughness steel
By using silicon dioxide-metal organic frame composite materials and epoxy-based hyperbranched polymers on high-strength high-strength steel, and combined with soaking and nitriding treatment in sodium hydroxide solution, the problem of high-strength high-strength high-strength steel is solved, and the effect of significantly improving corrosion resistance and mechanical properties is achieved.
Patent Information
- Application Number
- CN202411164534.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-23
AI Technical Summary
High-strength and high-strength steel is prone to corrosion and rust in corrosive environments, resulting in reduced strength and structural damage, affecting engineering safety.
A processing process is adopted, including the preparation of anticorrosion coatings using silica-metal organic frame composites and epoxy-based hyperbranched polymers, and spraying them on the surface of the steel strip, combined with soaking and nitriding in sodium hydroxide solution to improve the corrosion resistance of the steel.
It significantly improves the corrosion resistance and mechanical properties of high-strength and high-strength steel, extends the service life of the steel in a corrosive environment, and enhances the safety of the structure.
Smart Images

Figure BDA0005007447800000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-strength and high-toughness steel, and in particular to a processing technology and application of high-strength and high-toughness steel. Background Art
[0002] High-strength and high-toughness steel has higher tensile strength than ordinary steel. It can still maintain good plasticity under high stress and prevent brittle fracture. High-strength and high-toughness steel can significantly improve the load-bearing capacity and safety of the structure. Therefore, in modern industry, high-strength and high-toughness steel is widely used due to its excellent mechanical properties and durability.
[0003] However, in many harsh environments, especially those involving corrosive media, although high-strength and high-toughness steel has certain strength and toughness, long-term exposure to corrosive environments will not only reduce the strength of the steel, but also damage the steel structure. The steel is prone to corrosion and rust, thus affecting the safety of the overall project. Therefore, the development of a corrosion-resistant high-strength and high-toughness steel has become an important direction of material science research.
[0004] In order to solve the above problems and improve the mechanical properties and corrosion resistance of high-strength and high-toughness steel, the present invention provides a processing technology and application of high-strength and high-toughness steel. Summary of the invention
[0005] The purpose of the present invention is to provide a processing technology and application of high-strength and high-toughness steel to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A processing technology for high-strength and high-toughness steel comprises the following steps:
[0008] Step 1: Take a silica-metal organic framework composite material and N, N-dimethylformamide, stir evenly, add benzotriazole, stir for 6-7 hours, add an epoxy hyperbranched polymer, heat to 60-65°C and react for 7-9 hours, filter, wash and dry to obtain a modified silica-metal organic framework composite material;
[0009] Step 2: Take toluene and butyl acetate, add epoxy resin, stir evenly, add modified silica-metal organic framework composite material, heat to 75-80°C, react for 1-2h, cool to 25-30°C, add dibutyltin dilaurate, stir for 20-30min, add isocyanate curing agent, stir evenly, and obtain anticorrosion coating;
[0010] Step 3: Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1100-1200°C, perform rough rolling and finish rolling, quench at 850-900°C, and temper at 250-300°C to obtain a steel strip;
[0011] Step 4: Soak the steel strip in a sodium hydroxide solution for 5-10 minutes, take it out, wash it, and then perform nitriding treatment at 480-500°C for 7-9 hours to obtain a treated steel strip;
[0012] Step 5: Take the treated steel strip, spray anti-corrosion coating on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0013] More optimally, the high-strength and high-toughness steel is composed of the following components in mass percentage: C: 0.2-0.35%, Cr: 0.5-1.0%, Ni: 1.0-3.0%, Mo: 2.0-3.0%, Mn: 1.0-2.0%, Si: 0.1-0.50%, Ti: 0.1-0.3%, Nb: 0.1-0.2%, Al: 0.01-0.04%, S: 0.01-0.02%, and the rest is Fe.
[0014] More optimally, the preparation method of the silica-metal organic framework composite material is: take nano-silicon dioxide and methanol, ultrasonically disperse, add 2-methylimidazole, stir evenly to obtain a mixed solution; take methanol and zinc nitrate hexahydrate, stir evenly, add the mixed solution, continue stirring for 22-26 hours, centrifuge, wash, and dry to obtain the silica-metal organic framework composite material.
[0015] More optimally, the preparation method of the nano-silicon dioxide is: take ethanol, ammonia water, and deionized water, stir evenly, add tannic acid, stir for 20-30 minutes, add ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide.
[0016] More optimally, the preparation method of the epoxy hyperbranched polymer comprises the following steps:
[0017] S1: Take anhydrous methanol and diethanolamine, pass nitrogen, stir evenly, add methyl acrylate dropwise, heat to 35-40°C, keep warm for 4-5h, and distill under reduced pressure to obtain compound A; take trimethylolpropane and p-toluenesulfonic acid, stir evenly, heat to 115-120°C, add compound A, react for 5-6h, cool to 100°C, react for 60-90min, and obtain compound B;
[0018] S2: Take compound B and N,N-dimethylformamide, stir evenly, add boron trifluoride etherate and epichlorohydrin, react at 60-70°C for 2-3h, distill under reduced pressure, add sodium hydroxide solution, heat to 75-80°C, react for 3-4h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer.
[0019] More optimally, the mass ratio of the silica-metal organic framework composite material, benzotriazole, and epoxy hyperbranched polymer is 2:(5-7):(2-3).
[0020] More optimally, in step 4, after nitriding treatment, the thickness of the nitriding layer is 8-10 μm.
[0021] More optimally, high-strength and high-toughness steel is used in aerospace, construction fields, and cryogenic storage tanks.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] (1) The present invention uses C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, and Fe as raw materials to prepare a steel strip with excellent mechanical properties, and then further improves its wear resistance and mechanical properties by nitriding the steel.
[0024] (2) In the preparation of nano-silica, tannic acid is added as a pore-forming agent, which increases the specific surface area of the nano-silica, so that it has more active sites for grafting metal organic framework composite materials, thereby enhancing the corrosion resistance of the coating.
[0025] (3) The present invention combines the silica-metal organic framework composite material together to solve the problem that silica is easy to agglomerate, and then enhances the corrosion resistance by loading benzotriazole. The present invention prepares an epoxy hyperbranched polymer, and uses the epoxy hyperbranched polymer to perform epoxy group modification on the silica-metal organic framework composite material, so that the modified silica-metal organic framework composite material has better dispersibility in the epoxy resin anti-corrosion coating, further enhancing the corrosion resistance of the coating. The present invention controls the mass ratio of the silica-metal organic framework composite material, benzotriazole, and epoxy hyperbranched polymer to 2: (5-7): (2-3), at which time the corrosion resistance is optimal. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The sources and models of the raw materials involved in the present invention are not particularly limited, and exemplary examples include: epoxy resin: epoxy resin E-44; isocyanate curing agent: can be purchased from Hubei Nona Technology Co., Ltd., model: N0095.
[0028] Embodiment 1: A processing technology for high-strength and high-toughness steel, comprising the following steps:
[0029] Step 1: Preparation of nano-silicon dioxide:
[0030] Take 60 mL of ethanol, 24 mL of 0.02 mol / L ammonia water, and 200 mL of deionized water, stir evenly, add 1 g of tannic acid, stir for 25 min, add 10 mL of ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide;
[0031] Step 2: Preparation of silica-metal organic framework composite materials:
[0032] Take 2g of nano-silicon dioxide and 100mL of methanol, disperse by ultrasonication, add 4.5g of 2-methylimidazole, stir evenly to obtain a mixed solution; take 60mL of methanol and 1.5g of zinc nitrate hexahydrate, stir evenly, add the mixed solution, continue stirring for 24h, centrifuge, wash, and dry to obtain a silica-metal organic framework composite material;
[0033] Step 3: Preparation of epoxy hyperbranched polymer:
[0034] Take 10 mL of anhydrous methanol and 11 g of diethanolamine, pass nitrogen, stir evenly, add 17 g of methyl acrylate dropwise, heat to 38°C, keep warm for 4.5 hours, and distill under reduced pressure to obtain compound A; take 7 g of trimethylolpropane and 3 g of p-toluenesulfonic acid, stir evenly, heat to 118°C, add compound A, react for 5.5 hours, cool to 100°C, react for 70 minutes, and obtain compound B;
[0035] Take 12g of compound B and 5g of N,N-dimethylformamide, stir evenly, add 0.2g of boron trifluoride etherate and 2.5g of epichlorohydrin, react at 65°C for 2.5h, distill under reduced pressure, add 200mL of 25% sodium hydroxide solution, heat to 77°C, react for 3.5h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer;
[0036] Step 4: Preparation of modified silica-metal organic framework composite materials:
[0037] Take 2 g of silica-metal organic framework composite material and 100 mL of N,N-dimethylformamide, stir evenly, add 6 g of benzotriazole, stir for 6.5 h, add 2.5 g of epoxy hyperbranched polymer, heat to 62 ° C and react for 8 h, filter, wash and dry to obtain a modified silica-metal organic framework composite material;
[0038] The mass ratio of silica-MOF composite material, benzotriazole, and epoxy hyperbranched polymer is 2:6:2.5;
[0039] Step 5: Preparation of anti-corrosion coating:
[0040] Take 70 mL of toluene and 30 mL of butyl acetate, add 6 g of epoxy resin, stir evenly, add 3 g of modified silica-metal organic framework composite material, heat to 78 ° C, react for 1.5 hours, cool to 28 ° C, add 0.1 g of dibutyltin dilaurate, stir for 25 minutes, add 25 mL of isocyanate curing agent, stir evenly, and obtain an anti-corrosion coating;
[0041] Step 6: Preparation of high-strength and high-toughness steel:
[0042] Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1150°C, perform rough rolling and finish rolling, quench at 880°C, and temper at 270°C to obtain a steel strip, soak the steel strip in a 5% sodium hydroxide solution for 8 minutes, take it out, wash it, and then perform nitriding treatment at 490°C for 7.5 hours to obtain a treated steel strip; the thickness of the nitriding layer is 8μm;
[0043] In terms of mass percentage, it is composed of the following components: C: 0.25%, Cr: 0.8%, Ni: 2.0%, Mo: 2.5%, Mn: 1.5%, Si: 0.4%, Ti: 0.2%, Nb: 0.15%, Al: 0.03%, S: 0.015%, and the rest is Fe;
[0044] Take the treated steel strip, spray an anti-corrosion coating with a thickness of 25 μm on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0045] Embodiment 2: A processing technology for high-strength and high-toughness steel, comprising the following steps:
[0046] Step 1: Preparation of nano-silicon dioxide:
[0047] Take 60 mL of ethanol, 24 mL of 0.02 mol / L ammonia water, and 200 mL of deionized water, stir evenly, add 1 g of tannic acid, stir for 20 min, add 10 mL of ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide;
[0048] Step 2: Preparation of silica-metal organic framework composite materials:
[0049] Take 2g of nano-silicon dioxide and 100mL of methanol, disperse by ultrasonication, add 4.5g of 2-methylimidazole, stir evenly to obtain a mixed solution; take 60mL of methanol and 1.5g of zinc nitrate hexahydrate, stir evenly, add the mixed solution, continue stirring for 22h, centrifuge, wash, and dry to obtain a silica-metal organic framework composite material;
[0050] Step 3: Preparation of epoxy hyperbranched polymer:
[0051] Take 10 mL of anhydrous methanol and 11 g of diethanolamine, pass nitrogen, stir evenly, add 17 g of methyl acrylate dropwise, heat to 35°C, keep warm for 4 hours, and distill under reduced pressure to obtain compound A; take 7 g of trimethylolpropane and 3 g of p-toluenesulfonic acid, stir evenly, heat to 115°C, add compound A, react for 5 hours, cool to 100°C, and react for 60 minutes to obtain compound B;
[0052] Take 12g of compound B and 5g of N,N-dimethylformamide, stir evenly, add 0.2g of boron trifluoride etherate and 2.5g of epichlorohydrin, react at 60°C for 2h, distill under reduced pressure, add 200mL of 25% sodium hydroxide solution, heat to 75°C, react for 3h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer;
[0053] Step 4: Preparation of modified silica-metal organic framework composite materials:
[0054] Take 2g of silica-metal organic framework composite material and 100mL of N,N-dimethylformamide, stir evenly, add 5g of benzotriazole, stir for 6h, add 2g of epoxy hyperbranched polymer, heat to 60°C and react for 7h, filter, wash and dry to obtain a modified silica-metal organic framework composite material;
[0055] The mass ratio of silica-metal organic framework composite material, benzotriazole, and epoxy hyperbranched polymer is 2:5:2;
[0056] Step 5: Preparation of anti-corrosion coating:
[0057] Take 70 mL of toluene and 30 mL of butyl acetate, add 6 g of epoxy resin, stir evenly, add 3 g of modified silica-metal organic framework composite material, heat to 75 ° C, react for 1 hour, cool to 25 ° C, add 0.1 g of dibutyltin dilaurate, stir for 20 minutes, add 25 mL of isocyanate curing agent, stir evenly, and obtain an anti-corrosion coating;
[0058] Step 6: Preparation of high-strength and high-toughness steel:
[0059] Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1100°C, perform rough rolling and finish rolling, quench at 850°C, and temper at 250°C to obtain a steel strip, soak the steel strip in a 5% sodium hydroxide solution for 5 minutes, take it out, wash it, and then perform nitriding treatment at 480°C for 7 hours to obtain a treated steel strip; the thickness of the nitriding layer is 8μm;
[0060] In terms of mass percentage, it is composed of the following components: C: 0.2%, Cr: 0.5%, Ni: 1.0%, Mo: 2.0%, Mn: 1.0%, Si: 0.1%, Ti: 0.1%, Nb: 0.1%, Al: 0.01%, S: 0.01%, and the rest is Fe;
[0061] Take the treated steel strip, spray an anti-corrosion coating with a thickness of 25 μm on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0062] Embodiment 3: A processing technology for high-strength and high-toughness steel, comprising the following steps:
[0063] Step 1: Preparation of nano-silicon dioxide:
[0064] Take 60 mL of ethanol, 24 mL of 0.02 mol / L ammonia water, and 200 mL of deionized water, stir evenly, add 1 g of tannic acid, stir for 30 min, add 10 mL of ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide;
[0065] Step 2: Preparation of silica-metal organic framework composite materials:
[0066] Take 2g of nano-silicon dioxide and 100mL of methanol, disperse by ultrasonication, add 4.5g of 2-methylimidazole, stir evenly to obtain a mixed solution; take 60mL of methanol and 1.5g of zinc nitrate hexahydrate, stir evenly, add the mixed solution, continue stirring for 26h, centrifuge, wash, and dry to obtain a silica-metal organic framework composite material;
[0067] Step 3: Preparation of epoxy hyperbranched polymer:
[0068] Take 10 mL of anhydrous methanol and 11 g of diethanolamine, pass nitrogen, stir evenly, add 17 g of methyl acrylate dropwise, heat to 40°C, keep warm for 5 hours, and distill under reduced pressure to obtain compound A; take 7 g of trimethylolpropane and 3 g of p-toluenesulfonic acid, stir evenly, heat to 120°C, add compound A, react for 6 hours, cool to 100°C, react for 90 minutes, and obtain compound B;
[0069] Take 12g of compound B and 5g of N,N-dimethylformamide, stir evenly, add 0.2g of boron trifluoride etherate and 2.5g of epichlorohydrin, react at 70°C for 3h, distill under reduced pressure, add 200mL of 25% sodium hydroxide solution, heat to 80°C, react for 4h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer;
[0070] Step 4: Preparation of modified silica-metal organic framework composite materials:
[0071] Take 2g of silica-metal organic framework composite material and 100mL of N,N-dimethylformamide, stir evenly, add 7g of benzotriazole, stir for 7h, add 3g of epoxy hyperbranched polymer, heat to 65°C and react for 9h, filter, wash and dry to obtain a modified silica-metal organic framework composite material;
[0072] The mass ratio of silica-MOF composite material, benzotriazole, and epoxy hyperbranched polymer is 2:7:3;
[0073] Step 5: Preparation of anti-corrosion coating:
[0074] Take 70 mL of toluene and 30 mL of butyl acetate, add 6 g of epoxy resin, stir evenly, add 3 g of modified silica-metal organic framework composite material, heat to 80 ° C, react for 2 h, cool to 30 ° C, add 0.1 g of dibutyltin dilaurate, stir for 30 min, add 25 mL of isocyanate curing agent, stir evenly, and obtain an anticorrosive coating;
[0075] Step 6: Preparation of high-strength and high-toughness steel:
[0076] Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1200°C, perform rough rolling and finish rolling, quench at 900°C, and temper at 300°C to obtain a steel strip, soak the steel strip in a 5% sodium hydroxide solution for 10 minutes, take it out, wash it, and then perform nitriding treatment at 500°C for 9 hours to obtain a treated steel strip; the thickness of the nitriding layer is 8μm;
[0077] In terms of mass percentage, it is composed of the following components: C: 0.35%, Cr: 1.0%, Ni: 3.0%, Mo: 3.0%, Mn: 2.0%, Si: 0.50%, Ti: 0.3%, Nb: 0.2%, Al: 0.04%, S: 0.02%, and the rest is Fe;
[0078] Take the treated steel strip, spray an anti-corrosion coating with a thickness of 25 μm on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0079] Comparative Example 1: No tannic acid was added, and the rest was the same as Example 1:
[0080] Step 1: Preparation of nano-silicon dioxide:
[0081] Take 60 mL of ethanol, 24 mL of 0.02 mol / L ammonia water, and 200 mL of deionized water, stir evenly, add 10 mL of ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide;
[0082] Step 2: Preparation of silica-metal organic framework composite materials:
[0083] Take 2g of nano-silicon dioxide and 100mL of methanol, disperse by ultrasonication, add 4.5g of 2-methylimidazole, stir evenly to obtain a mixed solution; take 60mL of methanol and 1.5g of zinc nitrate hexahydrate, stir evenly, add the mixed solution, continue stirring for 24h, centrifuge, wash, and dry to obtain a silica-metal organic framework composite material;
[0084] Step 3: Preparation of epoxy hyperbranched polymer:
[0085] Take 10 mL of anhydrous methanol and 11 g of diethanolamine, pass nitrogen, stir evenly, add 17 g of methyl acrylate dropwise, heat to 38°C, keep warm for 4.5 hours, and distill under reduced pressure to obtain compound A; take 7 g of trimethylolpropane and 3 g of p-toluenesulfonic acid, stir evenly, heat to 118°C, add compound A, react for 5.5 hours, cool to 100°C, react for 70 minutes, and obtain compound B;
[0086] Take 12g of compound B and 5g of N,N-dimethylformamide, stir evenly, add 0.2g of boron trifluoride etherate and 2.5g of epichlorohydrin, react at 65°C for 2.5h, distill under reduced pressure, add 200mL of 25% sodium hydroxide solution, heat to 77°C, react for 3.5h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer;
[0087] Step 4: Preparation of modified silica-metal organic framework composite materials:
[0088] Take 2 g of silica-metal organic framework composite material and 100 mL of N,N-dimethylformamide, stir evenly, add 6 g of benzotriazole, stir for 6.5 h, add 2.5 g of epoxy hyperbranched polymer, heat to 62 ° C and react for 8 h, filter, wash and dry to obtain a modified silica-metal organic framework composite material;
[0089] The mass ratio of silica-MOF composite material, benzotriazole, and epoxy hyperbranched polymer is 2:6:2.5;
[0090] Step 5: Preparation of anti-corrosion coating:
[0091] Take 70 mL of toluene and 30 mL of butyl acetate, add 6 g of epoxy resin, stir evenly, add 3 g of modified silica-metal organic framework composite material, heat to 78 ° C, react for 1.5 hours, cool to 28 ° C, add 0.1 g of dibutyltin dilaurate, stir for 25 minutes, add 25 mL of isocyanate curing agent, stir evenly, and obtain an anti-corrosion coating;
[0092] Step 6: Preparation of high-strength and high-toughness steel:
[0093] Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1150°C, perform rough rolling and finish rolling, quench at 880°C, and temper at 270°C to obtain a steel strip, soak the steel strip in a 5% sodium hydroxide solution for 8 minutes, take it out, wash it, and then perform nitriding treatment at 490°C for 7.5 hours to obtain a treated steel strip; the thickness of the nitriding layer is 8μm;
[0094] In terms of mass percentage, it is composed of the following components: C: 0.25%, Cr: 0.8%, Ni: 2.0%, Mo: 2.5%, Mn: 1.5%, Si: 0.4%, Ti: 0.2%, Nb: 0.15%, Al: 0.03%, S: 0.015%, and the rest is Fe;
[0095] Take the treated steel strip, spray an anti-corrosion coating with a thickness of 25 μm on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0096] Comparative Example 2: No metal organic framework material is added, and the rest is the same as Example 1:
[0097] Step 1: Preparation of nano-silicon dioxide:
[0098] Take 60 mL of ethanol, 24 mL of 0.02 mol / L ammonia water, and 200 mL of deionized water, stir evenly, add 1 g of tannic acid, stir for 25 min, add 10 mL of ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide;
[0099] Step 2: Preparation of epoxy hyperbranched polymer:
[0100] Take 10 mL of anhydrous methanol and 11 g of diethanolamine, pass nitrogen, stir evenly, add 17 g of methyl acrylate dropwise, heat to 38°C, keep warm for 4.5 hours, and distill under reduced pressure to obtain compound A; take 7 g of trimethylolpropane and 3 g of p-toluenesulfonic acid, stir evenly, heat to 118°C, add compound A, react for 5.5 hours, cool to 100°C, react for 70 minutes, and obtain compound B;
[0101] Take 12g of compound B and 5g of N,N-dimethylformamide, stir evenly, add 0.2g of boron trifluoride etherate and 2.5g of epichlorohydrin, react at 65°C for 2.5h, distill under reduced pressure, add 200mL of 25% sodium hydroxide solution, heat to 77°C, react for 3.5h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer;
[0102] Step 3: Preparation of modified silica:
[0103] Take 2g of nano-silica and 100mL of N,N-dimethylformamide, stir evenly, add 6g of benzotriazole, stir for 6.5h, add 2.5g of epoxy hyperbranched polymer, heat to 62°C and react for 8h, filter, wash and dry to obtain modified silica;
[0104] The mass ratio of nano-silica, benzotriazole, and epoxy hyperbranched polymer is 2:6:2.5;
[0105] Step 4: Preparation of anti-corrosion coating:
[0106] Take 70 mL of toluene and 30 mL of butyl acetate, add 6 g of epoxy resin, stir evenly, add 3 g of modified silica, heat to 78 ° C, react for 1.5 hours, cool to 28 ° C, add 0.1 g of dibutyltin dilaurate, stir for 25 minutes, add 25 mL of isocyanate curing agent, stir evenly, and obtain an anticorrosive coating;
[0107] Step 5: Preparation of high-strength and high-toughness steel:
[0108] Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1150°C, perform rough rolling and finish rolling, quench at 880°C, and temper at 270°C to obtain a steel strip, soak the steel strip in a 5% sodium hydroxide solution for 8 minutes, take it out, wash it, and then perform nitriding treatment at 490°C for 7.5 hours to obtain a treated steel strip; the thickness of the nitriding layer is 8μm;
[0109] In terms of mass percentage, it is composed of the following components: C: 0.25%, Cr: 0.8%, Ni: 2.0%, Mo: 2.5%, Mn: 1.5%, Si: 0.4%, Ti: 0.2%, Nb: 0.15%, Al: 0.03%, S: 0.015%, and the rest is Fe;
[0110] Take the treated steel strip, spray an anti-corrosion coating with a thickness of 25 μm on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0111] Comparative Example 3: No epoxy hyperbranched polymer modification was used, and the rest was the same as Example 1:
[0112] Step 1: Preparation of nano-silicon dioxide:
[0113] Take 60 mL of ethanol, 24 mL of 0.02 mol / L ammonia water, and 200 mL of deionized water, stir evenly, add 1 g of tannic acid, stir for 25 min, add 10 mL of ethyl orthosilicate, stir evenly, wash, dry, and calcine to obtain nano-silicon dioxide;
[0114] Step 2: Preparation of silica-metal organic framework composite materials:
[0115] Take 2g of nano-silicon dioxide and 100mL of methanol, disperse by ultrasonication, add 4.5g of 2-methylimidazole, stir evenly to obtain a mixed solution; take 60mL of methanol and 1.5g of zinc nitrate hexahydrate, stir evenly, add the mixed solution, continue stirring for 24h, centrifuge, wash, and dry to obtain a silica-metal organic framework composite material;
[0116] Step 3: Preparation of benzotriazole-loaded silica-metal organic framework composite material:
[0117] Take 2 g of silica-metal organic framework composite material and 100 mL of N,N-dimethylformamide, stir evenly, add 6 g of benzotriazole, stir for 10 h, filter, wash and dry to obtain a silica-metal organic framework composite material loaded with benzotriazole;
[0118] Step 4: Preparation of anti-corrosion coating:
[0119] Take 70 mL of toluene and 30 mL of butyl acetate, add 6 g of epoxy resin, stir evenly, add 3 g of silica-metal organic framework composite material loaded with benzotriazole, heat to 78 ° C, react for 1.5 hours, cool to 28 ° C, add 0.1 g of dibutyltin dilaurate, stir for 25 minutes, add 25 mL of isocyanate curing agent, stir evenly, and obtain an anticorrosive coating;
[0120] Step 5: Preparation of high-strength and high-toughness steel:
[0121] Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1150°C, perform rough rolling and finish rolling, quench at 880°C, and temper at 270°C to obtain a steel strip, soak the steel strip in a 5% sodium hydroxide solution for 8 minutes, take it out, wash it, and then perform nitriding treatment at 490°C for 7.5 hours to obtain a treated steel strip; the thickness of the nitriding layer is 8μm;
[0122] In terms of mass percentage, it is composed of the following components: C: 0.25%, Cr: 0.8%, Ni: 2.0%, Mo: 2.5%, Mn: 1.5%, Si: 0.4%, Ti: 0.2%, Nb: 0.15%, Al: 0.03%, S: 0.015%, and the rest is Fe;
[0123] Take the treated steel strip, spray an anti-corrosion coating with a thickness of 25 μm on the surface, and solidify it to obtain high-strength and high-toughness steel.
[0124] experiment:
[0125] The high-strength and high-toughness steel prepared in Examples 1-3 and Comparative Examples 1-3 was used for performance testing, and the mechanical properties of the high-strength and high-toughness steel were tested with reference to GB / T 228.1 and GB / T22; the coating adhesion was tested by the cross-hatch method, and the test results were divided into 0-5 levels, where 0 means that the cutting edge is completely smooth and no grid falls off; 1 means that a small amount of coating falls off at the intersection, and the affected area cannot be significantly greater than 5%; the high-strength and high-toughness steel was cut into 150mm×100mm×1mm specimens, and then placed in a salt spray chamber at 35°C, with a sodium chloride concentration of 60g / L and a pH of 6.8-7.2, and the surface corrosion resistance was recorded. The data obtained are shown in the following table:
[0126]
[0127] Conclusion: In Comparative Example 1, tannic acid is not added, the specific surface area of nano-silica is small, the loaded metal-organic framework composite material is small, and the corrosion resistance is reduced. In Comparative Example 2, no metal-organic framework material is added, the loaded benzotriazole becomes less, and the corrosion resistance of the high-strength and high-toughness steel is reduced. In Comparative Example 3, epoxy hyperbranched polymer modification is not used, and the dispersibility of the silica-metal organic framework composite material in the epoxy resin anti-corrosion coating is poor, which affects the corrosion resistance of the coating and reduces the adhesion of the coating. The high-strength and high-toughness steel prepared by the method provided by the present invention has a yield strength greater than 1400MPa, a tensile strength greater than 1600MPa, an elongation after break greater than 45%, and excellent mechanical properties.
[0128] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for high-strength and high-toughness steel, characterized by: The following steps are involved: Step 1: Take a silica-metal organic framework composite material and N, N-dimethylformamide, stir evenly, add benzotriazole, stir for 6-7 hours, add an epoxy hyperbranched polymer, heat to 60-65°C and react for 7-9 hours, filter, wash and dry to obtain a modified silica-metal organic framework composite material; Step 2: Take toluene and butyl acetate, add epoxy resin, stir evenly, add modified silica-metal organic framework composite material, heat to 75-80°C, react for 1-2h, cool to 25-30°C, add dibutyltin dilaurate, stir for 20-30min, add isocyanate curing agent, stir evenly, and obtain anticorrosion coating; Step 3: Take C, Cr, Ni, Mo, Mn, Si, Ti, Nb, Al, S, Fe, smelt and cast to obtain a steel billet; then homogenize the steel billet at 1100-1200°C, perform rough rolling and finish rolling, quench at 850-900°C, and temper at 250-300°C to obtain a steel strip; Step 4: Soak the steel strip in a sodium hydroxide solution for 5-10 minutes, take it out, wash it, and then perform nitriding treatment at 480-500°C for 7-9 hours to obtain a treated steel strip; Step 5: Take the treated steel strip, spray anti-corrosion coating on the surface, and solidify it to obtain high-strength and high-toughness steel; The preparation method of the silica-metal organic framework composite material is as follows: taking nano-silicon dioxide and methanol, ultrasonically dispersing, adding 2-methylimidazole, stirring evenly to obtain a mixed solution; taking methanol and zinc nitrate hexahydrate, stirring evenly, adding the mixed solution, continuing to stir for 22-26 hours, centrifuging, washing, and drying to obtain the silica-metal organic framework composite material; The preparation method of the nano silicon dioxide is as follows: taking ethanol, ammonia water and deionized water, stirring evenly, adding tannic acid, stirring for 20-30 minutes, adding ethyl orthosilicate, stirring evenly, washing, drying and calcining to obtain the nano silicon dioxide.
2. The processing technology of high-strength and high-toughness steel according to claim 1 is characterized in that: The high-strength and high-toughness steel is composed of the following components in percentage by mass: C: 0.2-0.35%, Cr: 0.5-1.0%, Ni: 1.0-3.0%, Mo: 2.0-3.0%, Mn: 1.0-2.0%, Si: 0.1-0.50%, Ti: 0.1-0.3%, Nb: 0.1-0.2%, Al: 0.01-0.04%, S: 0.01-0.02%, and the rest is Fe.
3. The processing technology of high-strength and high-toughness steel according to claim 1 is characterized in that: The preparation method of the epoxy hyperbranched polymer comprises the following steps: S1: Take anhydrous methanol and diethanolamine, pass nitrogen, stir evenly, add methyl acrylate dropwise, heat to 35-40°C, keep warm for 4-5h, and distill under reduced pressure to obtain compound A; take trimethylolpropane and p-toluenesulfonic acid, stir evenly, heat to 115-120°C, add compound A, react for 5-6h, cool to 100°C, react for 60-90min, and obtain compound B; S2: Take compound B and N,N-dimethylformamide, stir evenly, add boron trifluoride etherate and epichlorohydrin, react at 60-70°C for 2-3h, distill under reduced pressure, add sodium hydroxide solution, heat to 75-80°C, react for 3-4h, distill under reduced pressure, filter, and obtain an epoxy hyperbranched polymer.
4. The processing technology of high-strength and high-toughness steel according to claim 1 is characterized in that: The mass ratio of the silicon dioxide-metal organic framework composite material, benzotriazole and epoxy hyperbranched polymer is 2:(5-7):(2-3).
5. The processing technology of high-strength and high-toughness steel according to claim 1 is characterized in that: In step 4, after nitriding treatment, the thickness of the nitriding layer is 8-10 μm.
6. High-strength and high-toughness steel obtained by processing according to the processing technology of high-strength and high-toughness steel according to any one of claims 1 to 5.
7. Application of the high-strength and high-toughness steel according to claim 6 in spacecraft, construction fields, and cryogenic storage tanks.
Citation Information
Patent Citations
Triglycidyl-isocyanurate-reinforced weather-resistant epoxy resin composite material for copper clad plates and preparation method thereof
CN106633668A
High-strength guide locking bolt for driving axle and manufacturing method of high-strength guide locking bolt
CN114561516A